Kuliah Kerja Nyata: Seminar dan Penyuluhan dalam Penyalahgunaan NAPZA Terhadap Masyarakat Desa Tigapanah - Dewi, Nurika Kartika; Harahap, Annisa Ihsani; Akhiriyah, Ikhtiari; Dinarta, Arya Rangga; Dalimunthe, Aryadanu; Hasibuan, Faqih Hakim (Pusdikra Publishing, 2025)
Community Service Learning (KKN) is a form of student dedication to society. This activity was carried out in Tigapanah Village by KKN students from the State Islamic University of North Sumatra, focusing on seminars and outreach regarding the abuse of Narcotics and Psychotropic Substances (NAPZA). This research aims to evaluate the effectiveness of the socialization program and community participation in understanding the negative impacts of NAPZA. The method used is an active participation approach, where students collaborate with village residents to convey information and education about the dangers of drugs. The results of the activity indicate that the community still has a knowledge gap regarding the abuse of NAPZA. It is hoped that this program will raise community awareness and encourage preventive actions against NAPZA abuse. The seminar and outreach are expected to have a sustainable positive impact in Tigapanah Village